2020
DOI: 10.1371/journal.pone.0238167
|View full text |Cite
|
Sign up to set email alerts
|

Infectivity and genes differentially expressed between young and aging theront cells of the marine fish parasite Cryptocaryon irritans

Abstract: The ciliated protozoan Cryptocaryon irritans infects a wide range of marine fish and causes the highly lethal white spot disease. This parasite possesses three morphologically and physiologically distinct life stages: an infectious theront, a parasitic trophont, and an asexually reproductive tomont. In the past few years, several attempts have been made to help elucidate how C. irritans transforms from one stage to another using transcriptomic or proteomic approaches. However, there has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…14,45,51 Shen et al 36 indicated that the loss of theront infectivity is associated with reduced swimming ability and body cilia number, and they speculated that energy attenuation is the main reason for the loss of infectivity. Chi et al 52 demonstrated that the genes related to energy production were down-regulated at 10 h compared with 1 h post-excystment.…”
Section: Life C Yclementioning
confidence: 99%
“…14,45,51 Shen et al 36 indicated that the loss of theront infectivity is associated with reduced swimming ability and body cilia number, and they speculated that energy attenuation is the main reason for the loss of infectivity. Chi et al 52 demonstrated that the genes related to energy production were down-regulated at 10 h compared with 1 h post-excystment.…”
Section: Life C Yclementioning
confidence: 99%
“…To date, no commercial vaccines against C. irritans are available, although good protection can be achieved by experimental vaccines using live, inactivated and subunit preparations and DNA vaccine candidates. Expressed sequence tag libraries of trophont, tomont and theront stages of C. irritans have been sequenced, 124,133,136 which will provide many opportunities for identification of diagnostic and protective antigens. We expect that this C. irritans transcription profiles will boost bioinformatic studies, including basic and applied discoveries.…”
Section: Discussionmentioning
confidence: 99%
“…The apoptosis-like death pathway has also been found in many protozoa, such as Leishmania, Plasmodium falciparum , Tetrahymena thermophila , Trypanosoma cruzi , Blastocystis hominis , Toxoplasma gondii , and Ichthyophthirius multifiliis [ 12 21 ], providing a new way to treat parasitic diseases. Many apoptosis-related genes of C. irritans have been found via transcriptome analysis [ 22 26 ], which indicates that C. irritans might have an apoptosis-like death pathway. Honokiol, one of the main active components of Magnolia officinalis , has been reported to induce apoptosis of cancer cells and Candida albicans via the endoplasmic reticulum (ER) stress pathway [ 27 30 ].…”
Section: Introductionmentioning
confidence: 99%